Effect of a multidisciplinary stress treatment programme on the return to work rate for persons with work-related stress. A non-randomized controlled study from a stress clinic - Bech Per; Netterstrøm Bo (BMC, 2010)
Abstract Background In recent years an increasing number of patients have been referred to the medical sector with stress symptoms. Moreover, these conditions imply increased sickness absence. This indicates a need for treatment programmes in general medical practice. The aim of this study was to test the effect of a multidisciplinary stress treatment programme on the return to work (RTW) rate in persons with work-related stress and establish predictive factors for this outcome. Methods During a two-year period 63 out of 73 referrals to the Stress Clinic (a section of a Clinic of Occupational Medicine) completed a stress treatment programme consisted of the following: 1) Identification of relevant stressors. 2. Changing the coping strategies of the participants. 3. Evaluating/changes in participant workload and tasks. 4. Relaxation techniques. 5. Physical exercise. 6. Psychiatric evaluation when indicated by depression test score. On average each patient attended six one-hour sessions over the course of four months. A group of 34 employees referred to the Clinic of Occupational Medicine by their general practitioners served as a control group. Each participant had a one-hour consultation at baseline and after four months. A specialist in occupational medicine carried out all sessions. Return To Work (RTW), defined as having a job and not being on sick leave at the census, was used as outcome measure four months after baseline, and after one and two years. Results The level of sick leave in the stress treatment group dropped from 52% to 16% during the first four months of follow-up and remained stable. In the control group, the reduction in sick leave was significantly smaller, ranging from 48% at baseline to 27% after four months and 24% after one year. No statistically significant difference between the two groups was observed after one and two years. Age below 50 years and being a manager increased the odds ratio for RTW after one and two years, while gender and depression had no predictive value. Conclusions The stress treatment programme showed a significant effect on the return to work rate. The stress treatment programme seems feasible for general practitioners. Trial Registration ISRCTN04354658